Balance entre la biomasa aérea y el rendimiento de los clones de cacao (Theobroma cacao L.) Pma-12 y eet-801 en la zona de buena fe. - Velez Peñafiel, Mariuxi Katherine (2021)
The production of perennial crops is conditioned by the annual biomass generation capacity, which benefits its agricultural production and yield capacity, where cocoa is no exception. In order to establish the balance between the aerial biomass and the yield of the commercial cocoa clones (Theobroma cacao L.) PMA-12 and EET-801 in the Buena Fe area. A completely randomized block design was proposed, with 2x3 factorial arrangement with four repetitions. Factor A refers to the cocoa clones PMA-12 and L12H27 and factor B to the initial tentative biomass levels in the crown (low, medium and high), and of each initial biomass level there will be four repetitions. For the comparison of the mean of the treatments, a Tukey test (p≤ 0.05) was used. The cocoa clones evaluated have been sown using the three-bobbin system, at a distance between plants of 3 m. For each clone, 12 trees were selected, which was done considering uniformity criteria (diameter and length of main trunk and branches, number of primary, secondary and tertiary branches). The entire experimental area was fertilized with Yara Mila Complex® which is composed of Nitrogen (N 12%), Phosphorus (P2O5 11%), Potassium (K2O 18%), Sulfur (S 11%), Magnesium (MgO 2.7%), Boron (B 0.015%), Iron (Fe 0.2%), Manganese (Mn 0.2%) and Zinc (0.2%), at a rate of 150 gr / plant / month. Likewise, during the dry season, soil moisture was maintained at localized irrigation capacity. Where the numerical components of the yield were measured every week for six months and as for the gravimetric components, the weight of ears and samples of the biomass generated were evaluated. It is observed that the initial biomass is conditioned to the final biomass, so it is concluded that determining the relationship between the biomass generated and the gravimetric components of the yield in the commercial cocoa clones, a better performance was demonstrated in the cultivar PMA 12 given that in its increase in biomass it reflects a good performance, leaving EET-801 with a criterion of resting state as it is not mentioned with significant changes in biomass production and in reproductive growth. Key words: Biomass, production, gravimetric components, yield, pruning.